473 LUNG ULTRASOUND IN CORONARY CARE UNIT, AN IMPORTANT DIAGNOSTIC TOOL FOR CONCOMITANT PNEUMONIA. (15th December 2022) - Chirico, Alfonsina; Basile, Christian; Mancusi, Costantino; Fucile, Ilaria; Mosca, Mariangela; Migliaccio, Biagio; Gargiulo, Giuseppe; Santoro, Ciro; Paolillo, Stefania; Perrone-filardi, Pasquale; Gargiulo, Paola
Abstract: Background: In the setting of coronary care unit (CCU), early detection of pneumonia is of para-mount important to prevent severe complications. This study was designed aiming to evaluate the diagnostic accuracy of lung ultrasound (LUS) in detection of pneumonia and compared with chest x-ray (CXR). Method: We enrolled 110 consecutive patients admitted to CCU of Federico II University Hospital. Each patient underwent CXR and bedside LUS on admission. The final diagnosis (pneumonia vs no-pneumonia) was established by another clinician reviewing clinical and laboratory data independent of LUS results and possibly prescribing chest contrast-enhanced CT (n=34). Results: Mean age was 70 ± 11 years old, 68% males. Pneumonia was clinically diagnosis in 26 (23%) patients. LUS was positive for pneumonia in 24 patients (sensitivity 92% specificity 81%). Chest radiography was positive in 9 patients (sensitivity 43% specificity 95%). Using CT scan as referee LUS exhibit 92% of sensibility and a specificity of 96%. In ROC curve analysis diagnostic accuracy of CXR and LUS for diagnosis of pneumonia was 0.86 (95% CI 0.77-0.94), higher than CXR 0.68 (95% CI 0.55-0.84), p<0.05 (Figure). Conclusion: Based on the findings of the present study, accuracy of LUS in detection of pneumonia was significantly higher than chest x-ray, with comparable sensibility to CT scan.